2015
DOI: 10.1136/bmjsem-2015-000048
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 12 weeks walking football on health and fitness in males over 50 years of age

Abstract: AimTo describe and characterise anthropometrical and fitness changes following a 12-week walking football programme in individuals over the age of 50 years.MethodsFollowing ethical approval, 10 male participants (mean (SD): age 66 (7) years) with a range of comorbidities completed a 12-week walking football programme, consisting of a single 2 h training session each week. Body mass, fat mass, fat free mass, maximal oxygen consumption, maximal heart rate, exercise time to exhaustion and isometric hand-grip stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 21 publications
(16 reference statements)
4
54
0
1
Order By: Relevance
“…Previous small-scale investigations have shown that walking football is a feasible and sustainable exercise intervention that may improve participants' mental wellbeing (Lamont, Harris, McDonald, Kerin, & Dickens, 2017;McEwan et al, 2019;Reddy et al, 2017), as well as their body composition and physical fitness (Arnold, Bruce-Low, & Sammut, 2015). An ethnographic study of walking football suggested that walking football also provides intangible benefits, including increasing participants' 'appetite for life' and enhancing their social engagement as part of a wider supportive community (Loadman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous small-scale investigations have shown that walking football is a feasible and sustainable exercise intervention that may improve participants' mental wellbeing (Lamont, Harris, McDonald, Kerin, & Dickens, 2017;McEwan et al, 2019;Reddy et al, 2017), as well as their body composition and physical fitness (Arnold, Bruce-Low, & Sammut, 2015). An ethnographic study of walking football suggested that walking football also provides intangible benefits, including increasing participants' 'appetite for life' and enhancing their social engagement as part of a wider supportive community (Loadman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effective strategies aimed at promoting healthy ageing and the prevention of chronic conditions are therefore highly desirable. Walking football (soccer) has recently emerged as a physical activity (PA) targeted at older adults, and particularly males over 50 (Arnold, Bruce-Low, and Sammut, 2015;Reddy et al, 2017); however, further research is required to examine the feasibility and attraction of this form of PA within such cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have been conducted on the impact of walking football on physiological measures of wellbeing, little detail is provided regarding the demographic of participants (Arnold, Bruce-Low, and Sammut, 2015;Reddy et al, 2017). Furthermore, these studies either involved mixed gender participants or only attracted those aged over 60, thus whether this form of intervention would be suitable and attractive to younger male participants (aged 50) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Walking football is experiencing large growth in participation within the UK, with approximately 1200 registered clubs in the UK (Walking Football Association, 2018). Research concerning the physical benefits of walking football has been conducted in general populations (Arnold, Bruce-Low, Sammut, & Arnold, 2015;Reddy et al, 2017) and also with those living with mental health conditions (Lamont, Harris, McDonald, Kerin, & Dickens, 2017). Results found physical changes such as significantly lower body fat mass (p=<0.05) (Arnold et al, 2015) after 12-…”
mentioning
confidence: 99%